Physical Fitness Profile of Students in terms of Student Activities in Sports - Daffa Hafizh Rizqika Rizal; Nur Subekti; Muhammad Tafwidh Alzaid (CV. FOUNDAE, 2022)
The fatigue experienced by junior high school (SMP) students while doing activities for a moment indicates that the students are not fit. Therefore, improving fitness to do more activities at a productive age is necessary. The purpose of this research was to determine the physical fitness profile of students in terms of sports activities. The quantitative description was the method of this research. The data collection technique used was the Indonesian Physical Fitness Test. The results showed that the fitness level of SMP Sekolah Alam Indonesia students was 0% in the excellent and good category, 31 percent in the medium category, 36 percent in the low category, and 33 percent in the poor category. The calculation obtained a significance value of more than 0.05, meaning the sample variance was normal. Thus, the hypothesis that the variance of the existing variables was the same was accepted. To determine whether there was a difference between sports activities and the fitness profile of SMP SAI students, the researchers performed the independent sample t-test on the data taken from the Indonesian Physical Fitness Test. The obtained significance value was 0.000 (less than 0.05). Therefore, it can be interpreted that there was a significant difference between the Fitness Profile of SMP SAI students and sports activities. In conclusion, the 8th-grade students of the school have not yet reached the good and excellent categories. The more active students are in exercising, the better their physical fitness level will be.